Cartographies of Differences Interdisciplinary Perspectives - Vieten, Ulrike M.; Valentine, Gill (New Visions of the Cosmopolitan, 2016)
This volume investigates the process of learning how to live with individual and group differences in the twenty-first century and examines the ambivalences of contemporary cosmopolitanism. Engaging with the concept of 'critical cartography', it emphasizes the structural impact of localities on the experiences of those living with difference, while trying to develop an account of the counter-mappings that follow spatial and social transformations in today's world. The contributors focus on visual, normative and cultural embodiments of difference, examining dynamic conflicts at local sites that are connected by the processes of Europeanization and globalization. The collection explores a wide range of topics, including conflicting claims of sexual minorities and conservative Christians, the relationship between national identity and cosmopolitanism, and the ways that cross-cultural communication and bilingualism can help us to understand the complex nature of belonging. The authors come from a variety of disciplinary backgrounds and all contribute to a vernacular reading of cosmopolitanism and transnationalism, aimed at opening up new avenues of research into living with difference.